Reduced GABA levels correlate with cognitive impairment in patients with relapsing-remitting multiple sclerosis - Cao, Guanmei; Edden, Richard A. E.; Gao, Fei; Li, Hao; Gong, Tao; Chen, Weibo; Liu, Xiaohui; Wang, Guangbin; Zhao, Bin (European radiology, 2018)
Objectives To investigate if brain gamma-aminobutyric acid (GABA) levels in patients with relapsing-remitting multiple sclerosis (RRMS) are abnormal compared with healthy controls, and their relationship to cognitive function in RRMS. Methods Twenty-eight RRMS patients and twenty-six healthy controls underwent magnetic resonance spectroscopy (MRS) at 3-T to detect GABA signals from posterior cingulate cortex (PCC), medial prefrontal cortex (mPFC) and left hippocampus using the ‘MEGAPoint Resolved Spectroscopy Sequence’ (MEGA-PRESS) technique. All subjects also underwent a cognitive assessment. Results In RRMS patients, GABA+ were lower in the PCC ( p = 0.036) and left hippocampus ( p = 0.039) compared with controls, decreased GABA+ in the PCC and left hippocampus were associated with specific cognitive functions (r = -0.452, p = 0.016 and r = 0.451, p = 0.016 respectively); GABA+ in the mPFC were not significantly decreased or related to any cognitive scores ( p > 0.05). Conclusions This study demonstrates that abnormalities of the GABAergic system may be present in the pathogenesis of RRMS and suggests a potential link between regional GABA levels and cognitive impairment in patients with RRMS. Key points • GABA levels may decrease in patients with RRMS . • Lower GABA levels correlated with worse cognitive performance in patients with RRMS . • Dysfunctional GABAergic neurotransmission may have a role in cognitive impairment in RRMS .